Insulin Use and The Risk of Hepatocellular Carcinoma: Insights and Implications - Juferdy Kurniawan; Maria Teressa (Interna Publishing, 2024)
In recent years, the incidence of diabetes mellitus and hepatocellular carcinoma (HCC) has been increasing worldwide, in the context of an increasing prevalence of non-alcoholic fatty liver disease (NAFLD). In patients with diabetes mellitus, exogenous insulin is commonly prescribed and used in long-term settings. Recent studies suggest that insulin use may elevate the risk of HCC. A substantial body of work seeks to unpack the association between insulin use and the risk of developing HCC, although there may be conflicting evidence. Further validation is necessary to clarify the true relationship between insulin mechanisms and its hepatocarcinogenic effect. Given the burden of diabetic patients developing HCC, diabetologists and hepatologists must collaborate, particularly regarding the prevention and surveillance of HCC in diabetic patients.